Genetics of psycho-emotional well-being: genome-wide association study and polygenic risk score analysis - Yakovchik, Anna Yurievna; Tolynyova, Darya V.; Kashtanova, Daria A.; Sutulova, Ekaterina R.; Ivanov, Mikhail V.; Mamchur, Alexandra A.; Erema, Veronika V.; Matkava, Lorena R.; Terekhov, Mikhail V.; Rumyantseva, Antonina M.; Blinova, Olga I.; Akinshina, Aleksandra I.; et al. (Frontiers in Psychiatry, 2024)
Background. Psycho-emotional well-being is essential for living a life of satisfaction and fulfillment. However, depression and anxiety have become the leading mental health issues worldwide, according to the World Health Organization. Both disorders have been linked to stress and other psychological factors. Their genetic bases disorders remain understudied. Methods. In 2020–2021, the psycho-emotional well-being of 30,063 Russians with no known psychiatric history was assessed using the Hospital Anxiety and Depression Scale (HADS) for general mental health and the HADS subscale A (anxiety) for anxiety. Following the original instructions, an anxiety score of ≥ 11 points was used as an anxiety threshold. Genome-wide association study was performed to find associations between anxiety and HADS/HADS-A scores using linear and logistic regressions based on HADS/HADS-A scores as binary and continuous variables, respectively. In addition, the links between anxiety, sociodemographic factors (such as age, sex, employment) , lifestyles (such as physical activity, sleep duration, and smoking), and markers of caffeine and alcohol metabolism were analyzed. To assess risk of anxiety, polygenic risk-score modeling was carried out using open-access software and principal component analysis (PCA) to simplify the calculations (ROC AUC = 89.4 ± 2.2% on the test set). Results. There was a strong positive correlation between the HADS/HADS-A scores and the sociodemographic factors and lifestyle. New single nucleotide polymorphisms (SNPs) with genome-wide significance were discovered, which had not been associated with anxiety or other stress-related conditions but were located in genes previously associated with bipolar disorder, schizophrenia, or emotional instability. The CACNA1C variant rs1205787230 was associated with clinical anxiety (a HADS-A score of ≥ 11 points). There was an association between anxiety levels (HADS-A scores) and genes involved in the activity of excitatory neurotransmitters: PTPRN2 (rs3857647), DLGAP4 (rs8114927) and STK24 (rs9517326). Conclusion. Our results confirm that calcium channels and monoamine neurotransmitters are involved in the development of increased anxiety, as well as SNPs in genes directly or indirectly affecting neurogenesis and synaptic functions. The role of some non-genetic factors and the clinical significance of physiological markers, such as lifestyle, has also been confirmed.